Effects of pressure garments of varying designs on upper extremity sensorimotor functions and quality of life after stroke: Study protocol for a multicenter, double-blind, prospective randomized controlled trial - Zhenkun Xu; Siaw Chui Chai; Shin Ying Chu; Kuicheng Li (PLoS ONE, 2025)
Rationale Stroke often results in extensive neurological damage, leading to a wide range of rehabilitation needs and challenges, with upper extremity dysfunction being particularly prevalent. Although pressure garments have been used in the rehabilitation of children with cerebral palsy to reduce muscle tone, their therapeutic effects have not been thoroughly investigated in the field of stroke. Aims To determine the effects of pressure garments with varying designs on stroke patients’ sensorimotor function and quality of life. Sample size estimate A total of 165 participants is required (55/group) with an effect size of 0.125, power of 0.80, alpha level of 0.05, and adjusted for a dropout rate of 20%. Methods and design This is a multicenter, double-blind, prospective randomized controlled, three-group trial. At three hospitals in Shandong, China, 165 patients within 1−12 months of stroke are randomly assigned (1:1:1) to receive Dorsal-Double-layered 10% circumferential reduction (DD-10, intervention), Single-layered 10% circumferential reduction (S-10, intervention), or Single-layered 0% circumferential reduction (S-0, placebo) pressure garments. Pressure garments are worn for 3 hours in the morning, 3 hours in the afternoon, and 8 hours at night daily for 8 weeks. During the first 4 weeks, patients also receive 30-min occupational therapy sessions. Study outcomes The primary outcome is the Fugl-Meyer Assessment of Upper Extremity to assess motor control. Secondary outcomes are the Box and Block Test (BBT) for assessing dexterity, Modified Ashworth Scale (MAS) for assessing muscle tone, Visual Analogue Scale for assessing pain, Disabilities of Arm, Shoulder, and Hand (DASH) for assessing self-perceived upper extremity function, and 36 Item Short Health Survey (SF-36) for assessing quality of life. Measurements are taken at Time 1(Baseline), Time 2 (Week 4), and Time 3 (Week 8). Discussion The expected outcome of this study is that it can determine the design of pressure garments best suited to improve sensorimotor function and the quality of life of stroke patients. It can also extend the clinical value of pressure garments and help healthcare professionals make more targeted treatment choices for stroke patients. Trial registration ClinicalTrials.gov Identifier: NCT06587308.